Larval development and foraging behavior of Erythrodiplax abjecta (Rambur) (Anisoptera: Libellulidae) in captivity (2020)
Understanding the life cycle of Neotropical odonate species is essential given our scant knowledge of this region.In this paper, we examine growth ratio between instars, development patterns, and active/passive feeding be-havior of the Andean dragonflyErythrodiplaxabjecta(Rambur, 1842). Larvae were obtained from eggs laid bytwo females in the laboratory and were maintained at 12–34 °C in individual containers until either theiremergence or their death. Larvae hatched 26–57 days after laying, and the total development time was de-termined as being 316 (SD ± 6.6) days, including 13 instars. Larval instars were characterized using sixmorphometric variables. The foraging behavior was analyzed considering the time of day and the percentage ofthe background covered by detritus. The growth ratios between successive instars averaged 1.9 for FW padlength, 1.6 for HW pad length and 1.2 for head width, head length, metathoracic leg length, and total length.Neither the active foraging nor the sit-and-wait foraging behavior were affected by either time of the day or thepercentage of background covered by detritus.Erythrodiplaxabjectais univoltine and has a slow lifestyle asso-ciated with lentic perennial waters, where larval development and growth rates are low. We provide an equationto estimate theE.abjectalarval instars from field specimens.Given that our results were obtained from the eggs laid by only two females, further studies including a largersample size are needed to validate their generality.